2018
DOI: 10.20546/ijcmas.2018.709.363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Groundnut + Millets Intercropping System on Yield and Economic Advantage in Central Dry Zone of Karnataka under Rainfed Condition

Abstract: A field experiment was conducted during Kharif 2017 at Zonal Agricultural and Horticultural Research Station, Babbur farm, Hiriyur to study effect of groundnut + millets intercropping system on yield and economic advantage in Central dry zone of Karnataka under rainfed condition. The experiment was laid out in randomized block design with ten treatments comprising of three millets viz., finger millet, little millet and foxtail millet with groundnut in the replacement series of 5:2 and 6:1 row proportion and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Manjunath et al (2018) reported that superiority of intercropping pigeonpea + foxtail millet (1:2) as higher net returns (` 111457 ha -1 ) and benefit cost ratio of 3.79 were recorded over sole cropping. Moreover, groundnut + foxtail millet (6:1) registered more land resource use efficiency as marginal increase of LER value (1.14) and higher B:C ratio (2.23) as against B:C ratio of sole groundnut of 2.14 and sole foxtail millet of 1.23 (Shwethanjali et al 2018). The studies clearly indicated yield advantages, efficient utilization of resources and economic returns with foxtail millet with different intercrop combinations.…”
Section: Cropping Systemmentioning
confidence: 78%
“…Manjunath et al (2018) reported that superiority of intercropping pigeonpea + foxtail millet (1:2) as higher net returns (` 111457 ha -1 ) and benefit cost ratio of 3.79 were recorded over sole cropping. Moreover, groundnut + foxtail millet (6:1) registered more land resource use efficiency as marginal increase of LER value (1.14) and higher B:C ratio (2.23) as against B:C ratio of sole groundnut of 2.14 and sole foxtail millet of 1.23 (Shwethanjali et al 2018). The studies clearly indicated yield advantages, efficient utilization of resources and economic returns with foxtail millet with different intercrop combinations.…”
Section: Cropping Systemmentioning
confidence: 78%
“…Manjunath et al [73] reported superiority of intercropping pigeonpea + foxtail millet (1:2) in obtaining higher net returns over sole cropping. Groundnut + foxtail millet (6:1) was found more successful over their sole planting (Shwethanjali et al [74]). In alfisols of Karnataka, little millet + pigeon pea intercropping (4:2) expressed highest little millet equivalent yield (LMEY).…”
Section: (C) Cultural Methodsmentioning
confidence: 99%
“…Sharmili and Parasuraman [75] reported that little millet + pigeonpea with 6:1 row ratio recorded greater LMEY in Tiruvannamalai district of Tamil Nadu during kharif season. Intercropping combination of groundnut and little millet (6:1) assured better resource use efficiency as LER and more B:C ratio (Shwethanjali et al [74]). The intercropping of finger millet with small onion intercrop had effective control over the weeds in finger millet over other intercroppings (Vishalini et al [66]).…”
Section: (C) Cultural Methodsmentioning
confidence: 99%
“…Sharmili and Parasuraman [67] also concluded that growing of little millet and pigeonpea in 6:1 row ratio with horsegram or mothbean in sequence have been found superior over other intercropping systems and also growing sole crop of little millet alone. Shwethanjali et [68] reported that Intercropping combination of groundnut and little millet (6:1) assured better resource use efficiency as LER (1.13) than pure stands of either groundnut or little millet and more B:C ratio of 2.16 and recorded groundnut equivalent yield (1,822 kg ha -1 ) which was at par with groundnut + little millet/finger millet under same row ratio. Shalini et al [49] and Sharmili and Manoharan [69] reported that the yield attributes of little millet like number of productive tillers per hill and test weight was found to be increased when intercropped with pigeon pea at 6:1 ratio and thus intercropping little millet and pigeon pea at proportions of 6:1 or 6:2 is beneficial.…”
Section: Intercropping In Little Milletmentioning
confidence: 99%